Campi universitários: desenvolvimento de suas estruturas espaciais - Ribeiro, André Luiz (2009)
The university campus is a space that has great importance in the development of the society. The formation of the knowledge in the university space is intrinsically related to all the set of elements in it: from the physical structure, to the knowledge and the people. The well understanding of what it means the physical structure of the campus will contribute strongly for this formation. The structures that compose the university campus and its own evolution passed through historical process analyses which are instruments of the process comprehension and relevance from its contribution in the society formation. This research analyzes campi from its characteristics applied in the monachal structures yet scholastic, the formation of the first universities and colleges in the Occidental Europe. Then, in the research s development, it slowly evaluates the campi of University of Virginia made by Jefferson, the Illinois Institute of Technology made by Mies van der Rohe and finally the Architecture s College of Porto in Porto University made by Alvaro Siza. The understanding of these structures will be certainty important in the project of new campi to be produced in XXI century.